2011
DOI: 10.1002/gcc.20892
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RARB2 identifies a dual role in cancer

Abstract: Two chemoprevention trials have shown that retinoic acid (RA) may be harmful in patients at risk for lung cancer, and RA administration to this high-risk group results in RARB2 reactivation. Although RARB2 is thought to possess tumor suppressive activity, its expression has recently been correlated with poorer prognosis in patients with nonsmall cell lung cancer. We hypothesized that RARB2 expression is necessary for the growth and maintenance of the oncogenic phenotype in lung cancer cells in which RARB2 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…RARb2 , a retinoic acid receptor, has a complex role in regulating cell proliferation, and although it generally plays a role in tumor suppression ( Yang et al . 2002 ), tumor promotion effects have also been described ( Pappas et al . 2011 ).…”
Section: Gene Methylation Patterns In Ctdna Linked To Prognosismentioning
confidence: 92%
“…RARb2 , a retinoic acid receptor, has a complex role in regulating cell proliferation, and although it generally plays a role in tumor suppression ( Yang et al . 2002 ), tumor promotion effects have also been described ( Pappas et al . 2011 ).…”
Section: Gene Methylation Patterns In Ctdna Linked To Prognosismentioning
confidence: 92%
“…A statistically significant restoration of RARβ expression and reduction of metaplasia were found in the 9-cis-RA group when compared to placebo (46). A recent study found a dual growth promoting and repressive role for RARβ2 in lung cancer cells, which may help explain the inconsistent results observed in clinical trials (47). …”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…RARβ2 is expressed in normal MECs, but is lost in most breast cancer cells and in most premalignant lesions and tumors, suggesting its tumor suppressor role ( 39 ). Activation of RARβ2 by retinoids or by epigenetic approaches, as well as by gene transduction to cells lacking the receptor may lead to decreased proliferation and increased senescence ( 40 , 41 ). Previously, we have identified a novel RARβ (β5) isoform (GenBank: AC133141.2 and AC098477.2) which has an independent P3 promoter and appears to play a dominant negative role in RARβ signaling ( 42 ).…”
Section: Rarβ Isoforms and Cellular Senescence In Breast Cancer Cementioning
confidence: 99%
“…Thus, in a recent study it was shown that antisense oligonucleotides against RARβ2 reduced proliferation and caused apoptosis in 3 lung cancer cell lines, but had no effect in 2 other cell lines lacking RARβ2, suggesting that RARβ2 may not only suppress, but also promote proliferative activity of tumor cells and thus plays a role of proto-oncogene ( 41 ). RARβ isoforms may directly or indirectly cooperate with other RARs and RXRs, ER, and other nuclear receptors (PPARβ/γ, vitamin D, thyroid) and thus affect cellular responses to retinoids and rexinoids ( 9 , 41 ). In most breast carcinomas RARβ is downregulated by hypermethylation of its promoter and/or by alterations of chromatin structure ( 39 , 46 ).…”
Section: Rarβ Isoforms and Cellular Senescence In Breast Cancer Cementioning
confidence: 99%